Metabolic Parameters and Adipokine Profile in Growth Hormone Deficient (GHD) Children Before and After 12-Month GH Treatment - Meazza, C.; Elsedfy, H. H.; Pagani, S.; Bozzola, E.; El Kholy, M.; Bozzola, M. (Hormone and Metabolic Research, 2014)
It is a common knowledge that GH exhibits a large number of metabolic effects, involving lipid and glucose homeostasis. The aim of the study was to investigate the effect of one year GH therapy on metabolic parameters and adipokines in GH deficient (GHD) children. Sixteen prepubertal children (11 M and 5 F) with complete GHD (age range: 3.4–14.7 years) and 20 (13 M and 7 F) age and sex-matched healthy children (age range: 4.6–12.3 years) were studied. Blood was collected from patients before starting GH therapy (0.025 mg/kg/day) and one year later, and from healthy children to measure adiponectin, leptin, osteoprotegerin, resistin, interleukin (IL)-6, tumor necrosis factor (TNF)-α levels, and other glucose and lipid metabolism parameters. Adiponectin and resistin levels were significantly higher (49 980 ng/ml vs. 14 790 ng/ml and 11.0 pg/ml vs. 6.3, respectively) in GHD children before GH therapy than in controls. Serum IGF-I levels (p=0.0001) and height SDS (p<0.0001) significantly increased after 12 months’ of GH therapy. There was a loss of body fat reflected by a significant decline in tricep (p=0.0003) and subscapular skinfold thickness SDS (p=0.0023). After 12 months, there was a significant rise in insulin (p=0.0052) and leptin levels (p=0.0048) and a significant decrease in resistin (p=0.0312) and TNF-α (p=0.0137). We observed that lipid and glucose metabolisms are only slightly affected in GHD children. Growth hormone replacement therapy affects some factors, such as leptin, resistin and fat mass, suggesting that also in children, GH treatment has a role in the regulation of factors secreted by adipose tissue.
Keywords: GH deficiency; GH therapy; adipokines; metabolism; children